NILAI MORAL YANG TERCERMIN DALAM NOVEL NGERI-NGERI SEDAP KARYA BENE D. RAJAGUKGUK - Karo Karo, Rehulina Bella Br; Martono, Martono; Seli, Sesillia (Universitas Tanjungpura, 2023)
This research aims to analyze the moral values contained in the novel Ngeri-Ngeri Sedap by Bene D. Rajagukguk. These moral values can be a lesson for readers. The moral values found are moral values that reflect the relationship between humans and God, humans and themselves, and humans and others. This study uses a descriptive method with a qualitative research form. This study uses a literary sociology approach. The research data source was obtained from the novel Ngeri-Ngeri Sedap by Bene D. Rajagukguk, with data in the form of words and sentences used as quotations. Data collection techniques used documentary study techniques, with the data collection tools being the researchers themselves and data card. The results of the first study: the moral value of the relationship between humans and God, namely being grateful, praying to God, and believing in God's destiny. Second: the moral values of human relations and oneself, namely responsibility, honesty, confidence, and guilt. Third: the moral values of human and neighbor relations, namely willingness to sacrifice, hope to make parents happy, love, and pride in parents. Fourth: a lesson plan has been prepared using the novel Ngeri-Ngeri Sedap as learning material based on KD 3.9 and 4.9 using an inquiry learning model based on HOTS, TPACK, 4C, and literacy.